Tác động của hành vi tiêu dùng cộng tác trên nền tảng kinh tế chia sẻ đến xu hướng mua ngẫu hứng - Lê Thị Thu , Mai; Hoàng Lê Phương , Mai; Lý Diệu , Linh; Lê Nguyễn Hồng , Nhật; Mai Phương , Anh; Nguyễn Quang , Danh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the impact of collaborative consumption on impulsive buying behavior on online sharing economy platforms in the context of travel clothing rental. Data were collected from 494 Generation Z consumers in Vietnam and analyzed using PLS-SEM with SmartPLS 3.0. Research results show that collaborative consumption significantly increases impulsive buying behavior. In addition, both uncertainty avoidance and moral identity weaken this relationship. The study extends the emerging discussion on the behavioral dark side of collaborative consumption by showing that this can activate impulsive buying in sharing economy platforms.